Bridging Theory and Practice: A Systematic Review of Work-Integrated Learning Frameworks in Vocational Education - Putra, Ricky Cahyasari; Barliana, Mokhamad Syaom; Komaro, Mumu; Hamdani, Aam (Journal of Vocational Education Studies, 2025)
Work-Integrated Learning (WIL) has become essential in vocational education for bridging academic learning with workplace experience. This systematic review analyzes 61 articles on WIL frameworks published between 2019-2024 using the PRISMA protocol. The analysis identifies five main types of WIL frameworks: Competency-Based Framework (focusing on industry-relevant competencies), Integrated Evaluation Framework (emphasizing comprehensive assessment), Industry-Academic Collaborative Framework (developing effective institutional-industry partnerships), Technology-Enhanced WIL Framework (utilizing technology to expand learning experiences), and Field-Specific Pedagogical Framework (tailoring approaches to specific disciplines). Publication trends show significant growth in WIL framework research, with a peak of 17 articles in 2024, reflecting increasing recognition of work-based learning's importance. The review reveals several research gaps, including limited investigation of technology integration's long-term impact, need for multi-stakeholder evaluation approaches, frameworks that effectively combine various WIL modalities, limited understanding of cross-disciplinary framework transferability, and frameworks that systematically incorporate evolving workforce demands. These findings provide direction for future WIL framework development and implementation, Contributing to more effective integration of academic learning with practical work experience in vocational education, these findings provide valuable direction for the future development and implementation of Work-Integrated Learning frameworks.